A microeconometric study of travelling behaviour - Gerd Ronning (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1989)
The paper reports on an attempt to analyse individual travelling behaviour by discrete choice models. It shows that among the socio-economic variables 'income (of household)' is the variable which influences the decision whether a trip is taken at all whereas 'age' seems to be the most important explanatory variable for the choice among foreign countries. The category-dependent variable 'purchasing power' mostly has the expected positive influence on the decision to travel abroad. The nested logit approach confirms that a simple multinomial logit approach disregards the dissimilarity between the alternative "domestic trip" and the choice set of foreign destinations. All results are based on a set of micro data taken from a German survey ("Reisea.nalyse") for the years 1975, 1980 and 1985.
Keywords: 330